An Enantiodivergent Synthesis of (+)‐ and (−)‐Centrolobines by Asymmetric Esterification Catalyzed by (R)‐(+)‐N‐Methylbenzoguanidine ((R)‐NMBG). Issue 11 (2nd October 2013) - Nakata, Kenya; Tokumaru, Tatsuya; Iwamoto, Hidetoshi; Nishigaichi, Yutaka; Shiina, Isamu
<x xml:space="preserve">Abstract</x> Seventh heaven: The enantiodivergent synthesis of (+)‐ and (−)‐centrolobines was achieved in a total of seven steps by using an asymmetric esterification in the presence of catalytic (R)‐(+)‐N‐methylbenzoguanidine as the key reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>